2022
DOI: 10.3389/fmicb.2022.1055638
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community diversity and function analysis of Aconitum carmichaelii Debeaux in rhizosphere soil of farmlands in Southwest China

Abstract: Understanding how microbial communities affect plant growth is crucial for sustainable productivity and ecological health. However, in contrast with the crop system, there is limited information on the microbial community associated with the medicinal plant. We observed that altitude was the most influential factor on the soil microbial community structures of Aconitum carmichaelii Debeaux. For community composition, bacterial reads were assigned to 48 phyla, with Proteobacteria, Acidobacteriota, and Actinobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with the distance decay principle, which suggests that as the geographical distance between two plant locations increases, the microbial communities of those plants grow increasingly dissimilar ( Hanson et al, 2012 ). Several studies have reported the impact of this distance decay on bacterial community composition ( Mosqueira et al, 2019 ; Pu et al, 2022 ; Sun et al, 2022 ). The frequent isolation of bacteria such as Pseudomonas, Pantoea, Curtobacterium , and Erwinia in this study is supported by studies investigating the culturable bacterial community of grapevines ( Bruez et al, 2015 ; Rezgui et al, 2016 ; Andreolli et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the distance decay principle, which suggests that as the geographical distance between two plant locations increases, the microbial communities of those plants grow increasingly dissimilar ( Hanson et al, 2012 ). Several studies have reported the impact of this distance decay on bacterial community composition ( Mosqueira et al, 2019 ; Pu et al, 2022 ; Sun et al, 2022 ). The frequent isolation of bacteria such as Pseudomonas, Pantoea, Curtobacterium , and Erwinia in this study is supported by studies investigating the culturable bacterial community of grapevines ( Bruez et al, 2015 ; Rezgui et al, 2016 ; Andreolli et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences in specific chemicals and equipment used, by incorporating modern measurement technology from the LD-GT1 Intelligent Soil Nutrient Analyzer (Shandong Lainde Intelligent Technology Co., Ltd., Shandong, China), we were able to execute these methods with greater efficiency and accuracy. Additionally, the LD-GT1 employs advanced sensing technology and automated processes for the effective quantification of OM content in soil, a methodology whose accuracy has been corroborated through scholarly research and practical application ( Pu et al, 2022 ). The determination of OM was carried out using the potassium dichromate dilution hot colorimetric method.…”
Section: Methodsmentioning
confidence: 99%